The social costs of underemployment : inadequate employment as disguised unemployment - Dooley, David (Cambridge University Press, 2004)
Comparing the effects of unemployment and inadequate employment relative to adequate employment, this text studies their effects on self-esteem, alcohol abuse, depression, and birth weight. Using longitudinal methods, it measures controls for reverse causation (selection) and studies a large representative sample of Americans from their late teens in 1979, to their early 30's in the last decade of the twentieth century through stages of different business cycles. The results point to a rethinking of employment status as a continuum. --Publisher.
Keywords: Underemployment.; Underemployment -- Health aspects.; Underemployment -- Psychological aspects.; Unemployment.; Health status indicators.; Unemployment; Socioeconomic Factors; Health Status Indicators; Unemployment -- statistics & numerical data; Unemployment -- psychology; Sous-emploi.; Sous-emploi -- Aspect sanitaire.; Sous-emploi -- Aspect psychologique.; Chômage.; Indicateurs de santé.; unemployment.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; POLITICAL SCIENCE -- Public Policy -- Social Security.; Underemployment; Underemployment -- Psychological aspects; Unterbeschäftigung; Psychologie; Arbeid.; Werkloosheid.; Verborgen werkloosheid.; Gezondheid.; Gezondheidseffecten.; Statistics; Statistics.; Statistiques.